Puerarin as a Phytochemical Modulator of Gastrointestinal Homeostasis in Livestock: Molecular Mechanisms and Translational Applications - Jiehong Zhou; Jianyu Lv; Xin Chen; Tian Li; Jianzhong Shen; Zhanhui Wang; Chongshan Dai; Zhihui Hao (Antioxidants)
The gut serves as the main site for nutrient digestion and absorption. Simultaneously, it functions as the body’s largest immune organ, playing a dual role in sustaining physiological equilibrium and offering immunological defense against intestinal ailments. Maintaining the structural and functional integrity of the intestine is paramount for ensuring animal health and productivity. Puerarin, a naturally derived isoflavonoid from the Pueraria species, exhibits multifaceted bioactivities, such as antioxidant, anti-inflammatory, antimicrobial, and immunomodulatory properties. Emerging evidence highlights puerarin’s capacity to enhance gut health in farm animals through four pivotal mechanisms: (1) optimization of intestinal morphology via crypt-villus architecture remodeling, (2) augmentation of systemic and mucosal antioxidant defenses through Nrf2/ARE pathway activation, and (3) reinforcement of intestinal barrier function by regulating tight junction proteins (e.g., ZO-1, occludin), mucin secretion, intestinal mucosal immune barrier, the composition of microbiota, and the derived beneficial metabolites; (4) regulating the function of the intestinal nervous system via reshaping the distribution of intestinal neurons and neurotransmitter secretion function. This review synthesizes current knowledge on puerarin’s protective effects on intestinal physiology in farm animals, systematically elucidates its underlying molecular targets (including TLR4/NF-κB, MAPK, and PI3K/Akt signaling pathways), and critically evaluates its translational potential in mitigating enteric disorders such as post-weaning diarrhea and inflammatory bowel disease in agricultural practices.